PROFILING PROPERTIES OF THE VERBS BRING, MAIL, SEND, ROB AND STEAL IN THE NEWS OF WASHINGTON POST AND PITTSBURG-GAZETTE - Dede Ismail (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2019)
This research is entitled Profiling Properties of the Verbs Bring, Mail, Rob and Steal in the News of Washington Post and Pittsburg-Gazette. The purpose of this research is to discuss the profiling properties of these verbs in the sentence-level construction which enables the writer to find out what kind of participant roles that are obligatorily profiled and not in that construction. The research is done by collecting some data containing ditransitive verbs in the news of Washington Post and Pittsburg-Gazette and even a single transitive verb in Pittsburg-Gazette, posted by the Corpus of Contemporary American English in 2006, 2014 and 2015. The result that can be taken from this research shows that (1) the direct object sometimes cannot be represented by inanimate in particular construction, (2) the direct object cannot be represented by any pronouns, except in the prepositional construction, and (3) the prepositional phrases, in some cases, are optionally profiled. Finally, profiling and not profiling participant roles may have something to do with what we called semantic restriction. Keywords: lexical profiling, constructional profiling, argument roles, ditransitive verb, inanimate, pronoun